PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN - Marsya Dzihnii Wahdaniyah; Titik Aryati (STMIK Widuri Jakarta, 2026)
The objective of this study is to examine the influence of firm size, institutional ownership, and independent board of commissioners on the financial performance of companies listed on the Indonesia Stock Exchange in the energy sector during the period 2022–2024. This study employs a quantitative method with purposive sampling and obtained 140 data points. Data analysis was conducted using panel regression with Eviews 12. The results indicate that firm size does not affect financial performance, whereas institutional ownership and the board of commissioners have a positive effect on financial performance. This suggests that good corporate governance plays a crucial role in enhancing a company’s financial performance.